2013
DOI: 10.1128/iai.00016-13
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Pfs25 Human Plasma Reduces Transmission of Plasmodium falciparum Isolates That Have Diverse Genetic Backgrounds

Abstract: f Pfs25 is a leading candidate for a malaria transmission-blocking vaccine whose potential has been demonstrated in a phase 1 trial with recombinant Pfs25 formulated with Montanide ISA51. Because of limited sequence polymorphism, the anti-Pfs25 antibodies induced by this vaccine are likely to have transmission-blocking or -reducing activity against most, if not all, field isolates. To test this hypothesis, we evaluated transmission-blocking activities by membrane feeding assay of anti-Pfs25 plasma from the Pfs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
1
23
0
4
Order By: Relevance
“…This agrees with the results from previous studies that also reported up to complete inhibition of oocyst formation using immune sera from animals immunized with different variants of Pfs 25 (Farrance et al, ; Gregory et al, ; Jones et al, 2013; Kaslow et al, ) or Pfs 230 (Farrance et al, ; Tachibana et al, ; Williamson et al, ). F0 therefore represents a very promising TBV candidate, featuring Pfs 25 as a highly‐conserved macrogamete/zygote antigen (Da et al, ) combined with the C0‐fragment of Pfs 230 as a relatively conserved gametocyte antigen (Foo et al, ; Williamson and Kaslow, ) that may benefit from boosting by natural reinfections partially compensating for the immune response bias towards Pfs 25 which will not be boosted during natural reinfection. The simple and efficient DSP procedure we developed underlines the potential of an economically‐feasible process for the transient expression of the vaccine candidate F0 in plants.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the results from previous studies that also reported up to complete inhibition of oocyst formation using immune sera from animals immunized with different variants of Pfs 25 (Farrance et al, ; Gregory et al, ; Jones et al, 2013; Kaslow et al, ) or Pfs 230 (Farrance et al, ; Tachibana et al, ; Williamson et al, ). F0 therefore represents a very promising TBV candidate, featuring Pfs 25 as a highly‐conserved macrogamete/zygote antigen (Da et al, ) combined with the C0‐fragment of Pfs 230 as a relatively conserved gametocyte antigen (Foo et al, ; Williamson and Kaslow, ) that may benefit from boosting by natural reinfections partially compensating for the immune response bias towards Pfs 25 which will not be boosted during natural reinfection. The simple and efficient DSP procedure we developed underlines the potential of an economically‐feasible process for the transient expression of the vaccine candidate F0 in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The many different systems, i.e., E. coli (10), tobacco (38,39), Saccharomyces cerevisiae (11,37,40,41), Pichia pastoris (12,42), DNA vaccines (43,44), wheat germ (15), insect cells via baculovirus (13,16), protein-peptide conjugates (45), Pseudomonas aeruginosa ExoProtein A (rEPA) (46), cholera toxin adjuvant (12), and virally vectored vaccines (47,48), by which recombinant Pfs25 has been produced have uniformly found that recombinant Pfs25 administered in animal models in the absence of adjuvant is poorly immunogenic, with relatively low IgG titers. The importance of a safe and effective adjuvant for Pfs25-regardless of the heterologous expression system-was highlighted in a phase I clinical trial in which Montanide IS151 combined with Pichia-produced Pfs25 was associated with leukemoid reactions and erythema nodosum in humans (21).…”
Section: Figmentioning
confidence: 99%
“…This approach was elegantly illustrated in a Phase 1 clinical trial with Pfs25 that was conducted in the US and where transmission blocking activity was induced in a minority of vaccinees, as detected by SMFA [51]. One serum sample was further tested in the DMFA using gametocyte isolates and mosquito colonies from Burkina Faso and Thailand [87]. These DMFA experiments confirmed the transmission blocking potential of vaccination against a range of genetically complex, naturally circulating parasite strains and illustrated the richness of information obtained with these biological assays early in clinical testing.…”
Section: Immunological and Mosquito Feeding Assays In Phase I Trialsmentioning
confidence: 99%